2010
DOI: 10.1039/b926192c
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-catalyzed [2+2+2] cycloaddition of various fluorine-containing alkynes—novel synthesis of multi-substituted fluoroalkylated aromatic compounds

Abstract: Treatment of various fluorinated internal alkynes with 10 mol% of RhCl(3).H(2)O and 30 mol% of i-Pr(2)NEt in toluene at the reflux temperature for 18 h gave the corresponding trimerization products as an isomeric mixture in high yields. Cycloaddition using 1.0 equiv. of fluorinated alkynes and 2.0 equiv. of non-fluorinated alkynes under the same reaction conditions as in the trimerization led to mono- and bis-fluoroalkylated benzene derivatives in high yields, together with small amounts of trimerization produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Methyl thiocyanate ( 1 m ) could also be applied successfully for this reaction (63%) under the modified reaction conditions using 100 mol% of Zn and 10 mol% of CoCl 2 (phen). It should be noted that various aliphatic nitriles which were not applicable in rhodium‐catalyzed system (Scheme 1, (b)), could also participate in the [2+2+2] cycloaddition well [9b] . When acetonitrile ( 1 n ) and isocapronitrile ( 1 o ) were used as a substrate, the corresponding trifluoromethylated pyridines 3 nA and 3 oA were obtained in 65% and 84% yield, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methyl thiocyanate ( 1 m ) could also be applied successfully for this reaction (63%) under the modified reaction conditions using 100 mol% of Zn and 10 mol% of CoCl 2 (phen). It should be noted that various aliphatic nitriles which were not applicable in rhodium‐catalyzed system (Scheme 1, (b)), could also participate in the [2+2+2] cycloaddition well [9b] . When acetonitrile ( 1 n ) and isocapronitrile ( 1 o ) were used as a substrate, the corresponding trifluoromethylated pyridines 3 nA and 3 oA were obtained in 65% and 84% yield, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Our research group has reported that the [2+2+2] cycloaddition of the trifluoromethylated diyne with some nitriles in the presence of rhodium chloride and diisopropylethylamine leads to the construction of the corresponding multi‐substituted pyridine derivatives (Scheme 1, (b)) [9b] . However, a rare metal, rhodium, is extremely expensive, and this reaction requires the use of 10 mol% of the transition metal as well.…”
Section: Introductionmentioning
confidence: 99%
“…A recent example of a lack of regioselectivity is found in the synthesis of multisubstituted fluoroalkylated aromatic compounds reported by Ishihara and colleagues. 29 Nonetheless, the reported rhodium(I)-catalyzed reaction is an interesting example of broadening the substrate scope of transition-metal-catalyzed [2+2+2]-cyclotrimerization reactions.…”
Section: Scheme 11 a Regioselective Cyclotrimerization Reaction Depenmentioning
confidence: 99%
“…21a,b Konno and co-workers reported that this rhodium(III) chloride plus amine system was also effective for the 1,2,4-selective [2+2+2] cycloaddition of trifluoromethyl-substituted arylacetylenes. 24…”
Section: Intermolecular Reactionsmentioning
confidence: 99%
“…The same catalyst could be used for the synthesis of trifluoromethyl-substituted benzenes by way of [2+2+2] cycloaddition, as reported by Konno and co-workers (Schemes 43 and 44). 24 Although the reaction of terminal diynes and a trifluoromethyl-substituted alkyne proceeded in low yields (Scheme 43), the reaction of trifluoromethyl-substituted unsymmetrical diynes and alkynes proceeded in good yields with moderate regioselectivity (Scheme 44).…”
Section: Scheme 42mentioning
confidence: 99%